Disentangling spring–neap suspended particulate matter (SPM) dynamics in estuaries - Y. M. Dijkstra; D. D. Bouwman; H. M. Schuttelaars (Ocean Science)
Suspended particulate matter (SPM) concentrations in estuaries have been observed to vary strongly over the spring–neap cycle through complex interactions between trapping and re-suspension. However, a systematic framework for analysing the processes causing this spring–neap SPM variability in general is missing. In this study we set up such a framework, consisting of three tiers. First, by studying the sediment transport capacity, how the locations of sediment trapping change over the spring–neap cycle is identified. Second, how the transport capacity affects the sediment stock and bottom pool of sediment is studied. This bottom pool only adapts gradually to the changing transport conditions, incorporating a lag or memory effect. Using a two-timescale analysis it is shown that this slow movement of the bottom pool is the leading source of such lag effects. Third, the SPM concentration is explained from an almost instantaneously balanced exchange between the bottom pool and the water column through re-suspension and deposition.